Relationship of Innovation and Sustainability in Supply Chain Context - Naseem, Aliya; Abbas, Rameesha (Advances in Social Sciences Research Journal, 2022)
Sustainability as a business phenomenon has occupied the attention of academicians, practitioners, and consumers for more than three decades. While some firms emphasize on their own internal sustainability initiatives, there is a growing trend to implement sustainability across the supply chain. This increasing interest makes implementation of sustainable supply chain management (SSCM) practices very important for focal firm’s sustainability; however, the ability to create innovative products, processes, and ways of operating is crucial if an organization is to be sustainable. Although there have been studies that investigate innovation in the context of sustainability, their scopes are limited to a single perspective which often obscures the big picture of innovation, its creation, and its effects on firm performance. In this study, we will adopt a multi-level innovation perspective to explore the symbiotic relationships between innovation creation and the development of SSCM practices, and resulting sustainability performance. This research will contribute to supply chain management and innovation literature and practice by identifying the different innovation types that emerge when SSCM practices are being implemented and explaining the effects innovation patterns and SSCM practices have on sustainability performance.